Relevance of Traditional Rituals and Food Culture: Study Based on Thiruvathirakali- a folklore festival of Kerala, India (International Journal of Food and Nutritional Sciences, 2022)
Kerala life was bound by different customs according to religion, caste, occupation and regional differences. Most of the Kerala customs were formed in the context of agricultural life. Therefore, different food culture existed according to the nature of each ritual. Diverse customs and food methods are also seen in connection with Thiruvathirakali, the ritual art of Kerala women. The aim of this study is to identify the unique relationship between the customs and food culture of Thiruvathira.